2009
DOI: 10.1002/ejic.200800933
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of a New Type of Chiral Bis(carbene) Ligand from L‐Valinol and Iridium(I) and Rhodium(I) Complexes Thereof

Abstract: New, chiral bis(imidazol‐2‐ylidene) ligands, and their rhodium(I) and iridium(I) complexes, have been prepared by a simple six‐step synthesis starting from commercially available enantiomerically pure L‐valinol. The stepwise introduction of the imidazoles makes it possible to create chiral bis(NHC) complexes with different substituents at the terminal nitrogen atoms. Formation of IrI and RhI complexes by a one‐pot transmetallation reaction gives the endo and exo stereoisomers in different ratios, depending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…[14] The appearance of the two signals (a') corresponding to the tert-butyl group of the minor isomer might be explained by agostic interactions between the C À H bond and the metal center, although we do not have any data to corroborate this hypothesis. A similar consideration was also reported by Nagel et al [15] In the 13 C NMR spectra, we observed a characteristic doublet at d = 196.7 ppm with a typical C-Rh coupling constant of 49.7 Hz for the carbene carbon atom.…”
supporting
confidence: 91%
“…[14] The appearance of the two signals (a') corresponding to the tert-butyl group of the minor isomer might be explained by agostic interactions between the C À H bond and the metal center, although we do not have any data to corroborate this hypothesis. A similar consideration was also reported by Nagel et al [15] In the 13 C NMR spectra, we observed a characteristic doublet at d = 196.7 ppm with a typical C-Rh coupling constant of 49.7 Hz for the carbene carbon atom.…”
supporting
confidence: 91%
“…An enantiomerically pure cyclopentadienyl-NHC carbene ligand (9) was recently prepared by reaction of a chiral imidazole tosylate derivative [21] with LiCp, followed by treatment with methyl iodide (Scheme 6). [22] This method is limited to unsubstituted cyclopentadienyl ligands since tetraalkylcyclopentadienyls are subject to lack of regioselectivity in their direct alkylation.…”
Section: Synthesis Of Cyclopentadienyl-and Its Annulated Indenyland Fmentioning
confidence: 99%
“…Cui and co-workers obtained the Sc (16, 20, 24) and Y (17,21) complexes by alkanolysis of [M(CH 2 SiMe 3 ) 3 (THF) 2 ] (M = Sc, Y) with the neutral Ind-and Flu-NHCs [generated in situ by treatment of the Ind-and Flu-imidazolium salts with Li(CH 2 SiMe 3 )]. Cui and co-workers obtained the Sc (16, 20, 24) and Y (17,21) complexes by alkanolysis of [M(CH 2 SiMe 3 ) 3 (THF) 2 ] (M = Sc, Y) with the neutral Ind-and Flu-NHCs [generated in situ by treatment of the Ind-and Flu-imidazolium salts with Li(CH 2 SiMe 3 )].…”
Section: Cyclopentadienyl- Indenyl-and Fluorenyl-functionalized Nhc mentioning
confidence: 99%
See 2 more Smart Citations